2014
DOI: 10.3389/fpsyg.2014.01154
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of social vs. non-social feedback on learning and generosity. Results from the Tipping Game

Abstract: Although much work has recently been directed at understanding social decision-making, relatively little is known about how different types of feedback impact adaptive changes in social behavior. To address this issue quantitatively, we designed a novel associative learning task called the “Tipping Game,” in which participants had to learn a social norm of tipping in restaurants. Participants were found to make more generous decisions from feedback in the form of facial expressions, in comparison to feedback i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…In contrast to WS, the ID group showed no clear effects of feedback type on behavioral measures or reinforcement learning parameters, demonstrating that the effects seen in WS are not explained by ID per se. Notably, the effects of social feedback seen in WS were also absent in the TD group in line with previous studies 32 , 33 , 35 . In this group, social as compared to non-social feedback reduced the likelihood of repeating a successful choice but did not affect the overall proportion of correct choices or reinforcement learning strategies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to WS, the ID group showed no clear effects of feedback type on behavioral measures or reinforcement learning parameters, demonstrating that the effects seen in WS are not explained by ID per se. Notably, the effects of social feedback seen in WS were also absent in the TD group in line with previous studies 32 , 33 , 35 . In this group, social as compared to non-social feedback reduced the likelihood of repeating a successful choice but did not affect the overall proportion of correct choices or reinforcement learning strategies.…”
Section: Discussionsupporting
confidence: 91%
“…These findings www.nature.com/scientificreports/ again suggest that social feedback has specific effects of reinforcement learning in WS, which are not seen in TD or ID. Previous research in TD has typically shown that social feedback enhances learning to a similar degree as symbolic non-social rewards, although results are somewhat mixed 30,35,36 . For example, one study reported worse probabilistic learning following social than non-social rewards 30 .…”
Section: Social Feedback Affects Loss/reward Balance In Wsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferential processing of social over non-social stimuli is commonly observed in healthy adult humans, while it is disrupted in schizophrenia, autism, and the rodent models of these disorders [22, 23, 24]. This bias is thought to result from a difference in reward values between social and non-social stimuli [25, 26]. Additionally, we investigated a simple approach behavior toward a stranger using the social approach test.…”
Section: Discussionmentioning
confidence: 99%
“…For example, healthy adults identify social stimuli much faster than nonsocial stimuli [1, 2] and have more difficulty disengaging from irrelevant social stimuli than from irrelevant nonsocial stimuli [3, 4]. People also appear to find social stimuli more rewarding; they show faster learning when feedback is social versus nonsocial stimuli [5, 6]. In addition to behavior, social and nonsocial stimuli are processed differently in the brain.…”
Section: Social Preference: the Way Humans Process Social Stimulimentioning
confidence: 99%